The determinants of economic resilience: Evidences from publicly listed firms in the Philippines - Bunag, Alyssa Nicole L. (Animo Repository, 2021)
Natural calamities are highly unpredictable events that could threaten and reduce the efficiency of firms. Previous studies on resilience have identified its determinants in relation to the supply chain, but few among those have attempted to use financial performance as indicators. In this study, financial ratios are used to identify the individual resilience of a firm and its characteristics. This is completed by using data from audited financial statements of publicly listed firms in the Philippines. The empirical results indicate that a low level of liquidity, a high level of leverage, and profitability correlates to a high level of resilience. The findings support that resilient firms are driven by the growth, innovation, and investments of their respective emerging sectors. Additionally, this study finds evidence that the location of a firm is not a significant factor that affects its ability to mitigate disruption.